PENGARUH RASIO LIKUIDITAS DAN RASIO LEVERAGE KEUANGAN TERHADAP PROFITABILITAS PERUSAHAAN - Hiba, Hakan; prasetyo, Andrian Budi (Diponegoro Journal of Accounting, 2024)
Covid-19 has directly and significantly impacted economic conditions, both in the real sector and the capital market. In the Capital Market, a stock index is often the target of investors, namely the LQ45 index. The LQ45 index is one of the stock index indicators on the Indonesia Stock Exchange, which can be used as a reference for assessing stock trading performance. The increase and decrease in the LQ45 Index is a benchmark for investors to invest their funds. One of the actions companies can take to make financial reports look better is increasing company profits (profitability). One of the indicators used in profitability ratios is return on assets (ROA) and return on equity (ROE). In addition, various factors can affect business profitability, including leverage and liquidity, measured using the current ratio. This study researched profitability in various industrial sector companies regarding liquidity, leverage, and company size. This research shows that the CR variable has a positive and significant influence on ROA. The DER variable has a negative and significant influence on ROA. The CR variable has no significant effect on ROE. DER has a negative and significant influence on ROE.